Early cognitive ability and emotional-behavioural development in childhood. (20th October 2021) - Bowe, A; Staines, A; Murray, D
Abstract: Background: Children with below average cognitive ability represent a substantial yet under-researched population for whom cognitive and social demands, which increase in complexity year by year, may pose significant challenge. This study compares trajectories in emotional-behavioural development for children with and without below average cognitive ability and examines the independent association between cognitive ability and clinically significant emotional-behavioural difficulty (EBD) in childhood. Methods: Participants consist of 7, 000 children and caregivers from the Growing Up in Ireland survey. Cognitive ability was measured at age 3 using the Picture Similarities Scale. A t-score 1-2 standard deviations below the mean was categorised as below average cognitive ability (n = 767), and scores above this as average/above (n = 6418). EBD was measured using the Strengths and Difficulties Questionnaire (SDQ) at age 3, 5 and 9 years. A generalised linear mixed model with repeated measures was used to examine the relationship between cognitive ability and SDQ. Logistic regression examined the independent association between cognitive ability and clinically significant EBDs between age 3-9 years. Results: The change in mean total SDQ score over time differed significantly between the cognitive ability groups (F(2)=8·817, p < 0·001). Between 5-9 years, there was no change in SDQ for those with average/above cognitive ability. For those with below average ability there was a significant increase of 0·48 points (95% CI 0·34 - 0·62, p < 0·001). After adjustment, the odds of a clinically significant EBD between age 3-9 were 1.4 times higher for those with below average cognitive ability (AOR 1.39, 95% CI 1.17-1.66, p < 0.001). Conclusions: Children with below average cognitive ability are at higher risk of EBD in childhood. A scalable method of early identification should be a research priority for public health, enabling early intervention for cognitive and adaptive outcomes. Key messages: Children with below average cognitive ability experience higher mean emotional-behavioural difficulty scores throughout childhood compared to those with average or above cognitive ability. Early life is a critical period for cognitive development. Public health research must focus on the early identification of at risk children to enable cognitive and adaptive functioning interventions.